IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Giawa, Yulina; Zagoto, Lidwina Shinta; Ritonga, Roy Ricardo; Manik, Efron; Hutauruk, Agusmanto J.B (JURNAL CURERE, 2024)
The Problem Based Instruction (PBI) learning model is a learning approach that uses real world problems as a context for students to learn how to think critically, problem solving skills, and to gain essential knowledge and concepts from the subject matter. This model is based on constructivist understanding and was developed to help students develop various skills. Mathematical problem solving ability is a component of ability that students must have in learning mathematics. One effort to address the problem of mathematical problem solving ability is through selecting a learning model. The Problem Based Instruction (PBI) model is a learning model that is based on many problems that require real investigation of real problems. This research aims to investigate differences in mathematical problem solving abilities between students who take part in learning using the Problem Based Instruction (PBI) model in junior high school students. This research is a Quasy Experimental research. Data analysis was carried out using the t-test for hypotheses 2 and 4, the t-test for hypothesis 1 and the Mann Whitney U test for hypothesis 3. The hypothesis results show that for the first hypothesis the tcount is more than ttable, for the second hypothesis the tcount is more than ttable, and for the third hypothesis, tcount is less than ttable, and for the fourth hypothesis, tcount is more than ttable. Based on the results of this research, it can be concluded that overall there is a difference in mathematical problem solving abilities between students who take part in learning using the Problem Based Instruction (PBI) model and students who take part in conventional learning among junior high school students. The results of this research can be used to improve students' mathematical problem solving abilities.